(untitled) (Citizenship in Action: Extension and Culture Magazine, 2023)
Academic League refers to a group of students and professors who, together, develop teaching, research and extension actions according to a certain theme. Therefore, the objective of this study is to report the actions developed by the Liga de Sexualidade between the years 2010 and 2020. For this, a survey was carried out, in which its general objective was to create a documentary collection of the Liga de Sexualidade da UFTM (LiS/ UFTM), from its inception in 2010 to 2020. Its specific objectives consistedof organizing the league’s documents; identify historical elements present in its constitution; describe the projects carried out in each administration and possible impacts on the beneficiary populations; investigate the relationship between student coordinators and professors regarding the planning and execution of activities; and contribute to the planning of current and future activities. To this end, documentary sources and oral sources were articulated through interviews with former teaching and student coordinators/coordinators. As a result, it was possible to collect a large amount of data and verify the importance of a historiographical research focused on extension programs –which can consider this research as a model. It was verified the importance of the articulation between documentary and oral sources, the documentation of the actions due to its relation with the memory of the oral sources and the emergence of the hybrid model as a possibility for the future.